2003
DOI: 10.1002/j.0022-0337.2003.67.4.tb03646.x
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Controlled Trials on the Effectiveness of Fluoride Gels for the Prevention of Dental Caries in Children

Abstract: Fluoride gels have been widely used since the 1970s. The aim of this review was to assess the effectiveness and safety of fluoride gels in the prevention of dental caries in children and to examine factors potentially modifying their effectiveness. Relevant randomized or quasi-randomized trials were identified without language restrictions by searching multiple databases, reference lists of articles, and journals and by contacting selected authors and manufacturers. Trials with blind outcome assessment compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
1
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 30 publications
1
20
1
4
Order By: Relevance
“…Moreover, these relative reductions are consistent with the overall PF's for D 3 MFS of clinical fluoride gel treatment studies in populations with higher caries activities than found in the present study, i.e. 22% (95% CI: 18–25%) (7) and 21% (95% CI: 14–28%) (8).…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, these relative reductions are consistent with the overall PF's for D 3 MFS of clinical fluoride gel treatment studies in populations with higher caries activities than found in the present study, i.e. 22% (95% CI: 18–25%) (7) and 21% (95% CI: 14–28%) (8).…”
Section: Discussionsupporting
confidence: 91%
“…The percentage of caries reduction in the experimental group was 76.5% on the occlusal surface, 85.5% on the buccal surface and 83.3% on the lingual surface. The percentage of caries reduction in the present study was higher than in other studies (14)(15)(16)(17)(18) and the results obtained from various reviews and meta-analysis (19)(20)(21). This could be attributed to the fact that in all the above studies and reviews, incipient lesions were not recorded.…”
Section: Discussioncontrasting
confidence: 78%
“…The value of dentist‐ or patient‐administered caries preventive agents is supported by a number of studies (1–4). In addition, current evidence supports their use as alternatives to restoration before demineralization has produced a cavitated lesion (5–7).…”
mentioning
confidence: 99%